Multiscale hybrid CNT and CF reinforced PEEK composites with enhanced EMI properties. Issue 1 (31st December 2022) - Cao, Shouyi; Tao, Yinping; Li, Hong; Ren, Musu; Sun, Jinliang
Abstract: Due to ever increasing use of telecommunication and electronic devices in offshore and stealth technology sectors, developing highly-efficient electromagnetic interference (EMI) shielding materials with good thermal resistance are urgently required. In this paper, the effect of MWCNTs incorporation on the mechanical, interlaminar bonding and EMI performance of MWCNT/CF/PEEK composites were firstly studied. The introduction of interlaminar MWCNTs did not affect the tensile strength and modulus significantly at low loadings whilst slight decrease in them was seen beyond a MWCNT content of 2.5 g/m 2 due to the presence of CNT clusters. Improvement in the flexural strength and modulus as well as interlaminar bonding were achieved, reaching the peak values at an interlaminar MWCNT content of 1.5 g/m 2 . This is because the existence of inter-ply CNTs improves the stiffness and strength of the interlaminar region in shear when the material is subjected to bending moment. EMI shielding effectiveness of the laminates was markedly enhanced by 76% at an interlaminar CNT content as low as 2.5 g/m 2 (equivalent to 0.53 wt.%). For the first time, this work has demonstrated the effectiveness and high efficiency of utilizing a multilayer structural design with the CNTs spray coated at the interlaminar region to improve the EMI shielding performance of CF/PEEK composites. Graphical Abstract: UF0001